Tindak Pidana Ujaran Kebencian Memakai Akun Palsu (Fake Account) Di Media Sosial - Ajeng Kartika Ayu; Alfitra Alfitra (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2019)
Abstract:The presence of the Law on Information and Electronic Transactions in Indonesia, is a tangible form of action taken by the government to deal with the development of technology and information development. This study explains the legal basis and application of law for hate speech perpetrators on social media through fake accounts in a positive legal perspective in Indonesia as well as what are the factors that cause perpetrators to use fake accounts to commit criminal acts of hate speech on social media. The approach used in this research is juridical normative through library research with qualitative research methods. The results of this study indicate that in addition to environmental factors, technological and information development factors also trigger offenders to commit crimes. The application of law that can be implemented in cases like this is through the law (court) or alternative dispute resolution through mediation of the law.Keywords: Hate Speech (Hate Speech), Fake Accounts, Social Media